Methicillin resistant Staphylococcus aureus (MRSA) carriage in different free-living wild animal species in Spain - Porrero, M. Concepción; Mentaberre, Gregorio; Sánchez, Sergio; Fernández Llario, Pedro; Gómez Barrero, Susana; Navarro Gonzalez, Nora; Serrano, Emmanuel; Casas Díaz, Encarna; Marco, Ignasi; Fernández Garayzabal, José Francisco; Mateos, Ana; Vidal, Dolors; et al. (My University, 2013)
Methicillin-resistant Staphylococcus aureus (MRSA) is a life-threatening pathogen in humans and its pres ence in animals is a public health concern. The aim of this study was to measure the prevalence of MRSA in free-living wild animals. Samples from red deer (n = 273), Iberian ibex (n = 212), Eurasian Griffon vul ture (n = 40) and wild boar (n = 817) taken from different areas in Spain between June 2008 and Novem ber 2011 were analyzed. Characterization of the isolates was performed by spa typing, multi-locus sequence typing (MLST) and antimicrobial susceptibility testing. A low prevalence of MRSA was found with 13 isolates obtained from 12 animals (0.89%; 95% CI: 0.46¿1.56). All MRSA sequence types belonged to ST398 (t011 and t1451) and ST1 (t127). Genotypes and antimicrobial susceptibility patterns (tetracycline resistance in ST398 and clindamycin¿erythromy cin¿tetracycline resistance in ST1) suggest that the MRSA found probably originated in livestock (ST398) or humans (ST1). This is the first report of MRSA carriers in free-living wild animals in Europe. Although our data showed that MRSA prevalence is currently low, free-living wild animals might act as reservoir and represent a potential risk for human health.